What Will the New Generation Generate? Gendering Accumulation in Fatou Diome’s Celles qui attendent - Christopher Hogarth (Studies in 20th & 21st Century Literature, 2014)
In this paper I focus on the penultimate installment of the oeuvre of the much-celebrated Franco-Senegalese writer Fatou Diome, whose largely autobiographical work has garnered a wide following and a lucrative contract with the Flammarion publishing house. I propose that Diome’s 2010 novel Celles qui attendent strongly contributes to a discourse surrounding the roles of males and females in an African economy increasingly dominated by migration. Diome started as a writer who portrayed the empowered role of the female migrant, who is able to accumulate financial capital in Europe and send it back to Africa in order for males to slowly hoard goods and start businesses. Her more recent work, however, has been marked by a shift to reflect a portrait of Senegalese society and migration that is backed by sociological studies: men take on the role of migrants, tempted by “marchands d’illusions” 'merchants of illusions,' but are also determined to get away from social pressures in order to accumulate their own set of experiences in the world, at a distance from the expectations of a traditional African society. Women, on the other hand, are left in extreme proximity to the problems of everyday life on a cash-starved continent, as they have to go about the business of surviving and raising children, engaging in many forms of hoarding that have to do with accumulating finance, memories and myths.
Keywords: Fatou Diome; accumulation; migration; gender; Africa; Francophone